Етранжизми в сучасній українській мові - Дюндик, О. (Лексикографічний бюлетень, 2015)
The article is analyzed new loans in the modern Ukrainian language. Two possible ways of response to new loans are considered: openness of language and tendency to purism. The experience of other Slavic languages is taken into consideration while analyzing purism, in particular Czech and Croatian. On the issue of linguistic evaluation of new loans major category is the necessity of these loans. There is a tendency that the English words and phrases recently actively fi ll up our lexicon than Russian. Sometimes it is not about borrowing new words and meanings, but about the displacement of Ukrainian words, which experts call “linguistic aggression”.